Pola Komunikasi Orang Tua Tunggal Dalam Membentuk Kemandirian Anak (Kasus di Kota Yogyakarta) - Y. Retnowati; A.V.S. Hubeis; Hadiyanto . (Institut Pertanian Bogor, 2008)
Communication is one aspect that can be considered in transforming children’s independency. The aims of thisresearch are: (1) examining communication pattern of single parents in transforming children’s independency; (2)analyzing the correlation between surroundings and the characteristic of single parents to communication pattern;(3) analyzing the correlation between surroundings and the characteristic of single parents to children’sindependency. This research employes qualitative approach and survey method by collecting data throughquestionnaires with 25 single parents who are determined by having legal documents issued by YogyakartaReligious Court, in-depth interview with 10 single parents. Then, data is analyzed descriptively. The results of thisresearch showed that: (1) the interaction and transaction communication pattern played a dominant role intransforming children’s independency by internalizing consciousness to be independent and giving children sometraining; (2) there is no correlation between surroundings factor and communication pattern but there is correlationbetween the characteristic of single parents and communication pattern; (3) there is correlation betweensurroundings factor and the characteristic of single parents to children’s independency.